Sequential Bilateral Cochlear Implantation in a Patient with Bilateral Meniere’s Disease - Holden, Laura K. (2012)
This case study describes a 45 year old female with bilateral, profound sensorineural hearing loss due to Meniere’s disease. She received her first cochlear implant in the right ear in 2008 and the second cochlear implant in the left ear in 2010. The case study examines the enhancement to speech recognition, particularly in noise, provided by bilateral cochlear implants. Speech recognition tests were administered prior to obtaining the second implant and at a number of test intervals following activation of the second device. Speech recognition in quiet and noise as well as localization abilities were assessed in several conditions to determine bilateral benefit and performance differences between ears. The results of the speech recognition testing indicated a substantial improvement in the patient’s ability to understand speech in noise and her ability to localize sound when using bilateral cochlear implants compared to using a unilateral implant or an implant and a hearing aid. In addition, the patient reported considerable improvement in her ability to communicate in daily life when using bilateral implants versus a unilateral implant. This case suggests that cochlear implantation is a viable option for patients who have lost their hearing to Meniere’s disease even when a number of medical treatments and surgical interventions have been performed to control vertigo. In the case presented, bilateral cochlear implantation was necessary for this patient to communicate successfully at home and at work.